Faktor-Faktor Yang Mempengaruhi Status Gizi Pada Remaja Di SMPN 12 Kuala Lempuing Kota Bengkulu - Sinaga, Maylina Dewi; Retni, Retni; Habibi, Julius (Jurnal Kesehatan Mitra Sekawan, 2025)
Nutritional status is a condition determined by the degree of physical need for energy and nutrients obtained from food and foods whose physical impacts can be measured. The prevalence of nutritional status (BMI/U) in Adolescents aged 13-15 years according to Bengkulu Province in 2018 found adolescents with very thin nutritional status of 1.0%, thin 6.5%, normal 75.9%, fat 12.6%, and obesity 3.9%. The prevalence of nutritional status (BMI/U) in adolescents aged 13-15 years in the city of Bengkulu in 2018 found adolescents with very thin nutritional status of 2.43%, thin 7.17%, normal 66.53%, obese 17.60%, and obesity 6.27%. This study aims to determine the factors that influence the nutritional status of adolescents at SMPN 12 Kuala Lempuing, Bengkulu City. This type of research is quantitative with a cross sectional design. The sample in this study amounted to 82 people, taken by random sampling. Data analysis was carried out using the chi-square test with a significance level of 95%. The results of the analysis show that the majority of students have poor nutritional status and lack of knowledge, the majority of students have poor eating patterns with poor nutritional status and some students have a positive body image with poor nutritional status. Based on bivariate analysis, the results showed that there was a significant relationship between knowledge and malnutrition status, there was a significant relationship between diet and malnutrition status and bivariate analysis on body image showed that there was no significant relationship between body image and malnutrition status in SMPN 12 Kuala Lempuing Bengkulu City. It is hoped that schools can provide more information about nutrition to teenage students at SMPN 12 Kuala Lempuing, Bengkulu City.